Phenylpropanolamine : analytical and pharmacokinetic studies using high-performance liquid chromatography - Scherzinger, Sabine Hilda (Rhodes University, Faculty of Pharmacy, Pharmacy, 1988)
Phenylpropanolamine (PPA), a synthetic sympathomimetic amine structurally related to ephedrine has been widely used over t he past 40 years as a nasal decongestant and appetite suppressant. It has been the focus of much controversy concerning the efficacy of the drug in its use as an anorectic agent, and due to the side effects caused by the higher doses of PPA required for appetite suppression. Although extensively used, there is little information concerning the determination of PPA in biological fluids and on the pharmacokinetics of this drug. An adaptation of a published high-performance liquid chromatographic (HPLC) assay for PPA in serum and urine using U.V. detection at 210 nm is presented. PPA was separated in the reversed phase mode. The method has a limit of sensitivity of 5.0 ng/mL and 10.0 ng/mL in serum and urine respectively. Serum concentration data following a single 25 mg dose of phenylpropanolamine in human volunteers demonstrate the application of the analytical method for bioavailability and pharmacokinetic studies. After the administration of 25 mg, 50 mg or 100 mg PPA.HCl solutions to 5 human volunteers, a dose proportionality study demonstrated that PPA appears to exhibit linear kinetics. Linear one body compartment kinetics were assumed and the wagner-Nelson method used to transform in vivo serum data to absorption plots. The serum data were fitted to a model using nonlinear regression techniques to characterize the pharmacokinetic processes of PPA. The absorption of phenylpropanolamine appears to be discontinuous and the drug seems to favour a two body compartment model. The pharmacokinetic parameters obtained from a steady state study using multiple dosing of PPA.HCl solutions compared with those found from previous studies after the administration of sustained-release formulations. A plasma protein binding study using equilibrium dialysis demonstrated that PPA is not highly protein bound in the blood.
Keywords: Phenylpropanolamine; Pharmacokinetics; High performance liquid chromatography